Phase relationships in the Al-rich region of the Al-Y-Zr system - Bao X.; Liu L.; Huang S.; Jiang Y.; Wang X.; Zhang L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The phase relations in the Al-Y-Zr ternary system at 873 K have been investigated by X-ray powder diffraction (XRD) and scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS) in backscattered electron imaging (BSE) modes. Six three-phase equilibria are determined and no ternary compound is observed. In the meantime, first principle calculations are used to provide theoretical guidance to understand the experimental results.